Ensemble Deep Learning Technique for Robust Seizure Detection ‎Using Integrating Convolutional and Recurrent Neural Networks ‎with Advanced Optimization Techniques - Kumar, K. Dileep; Dash, Dr. Sachikanta; A., Dr. Rajendra Kumar Ganiya (International Journal of Basic and Applied Sciences, 2025)
Electroencephalogram (EEG) is a common problem where seizures need to be detected in the ‎healthcare industry because the quality of life of a patient can be affected, and it can even ‎cause serious health issues. In this paper, a hybrid deep learning model combining ‎Convolutional Neural Networks (CNN) to capture spatial features and Long Short-Term ‎Memory (LSTM) RNNs to detect temporal dynamics in EEG signals is presented. Our model ‎was trained and tested on the CHB-MIT Scalp EEG Database, which has been used in many ‎studies on seizure detection. The hybrid CNN-LSTM structure does better than the ‎conventional CNN or LSTM structure and its accuracy is 94.3 %, its precision score is 92.9 ‎and it has a high recall score of 99.2 with F1 score of around CNN-only model, however, ‎performed a little better gaining 89.5 percent of accuracy along with only approximately 86.6 ‎percent of increase in F1 score. The LSTM has also performed badly with a range of 84-86%. ‎Moreover, after conducting the study, the research also takes a step further in determining ‎how robust these models are against adversarial attack by attacking them with attacks using ‎Fast Gradient Sign Method (FGSM). At 0.05, the accuracy was reduced which is expected to ‎happen to all models but the hybrid model had a lesser impact hence returning with 78:5% ‎inaccuracy. The hybrid model (0.833) had better robustness score compared to the CNN-only ‎and the LSTM-only model as in the case of main model results with MaxFillup. Adversarial ‎training also plays a critical role in enhancing the underpinnings of this hybrid model such that ‎when it was tested on clean data, it was tested robustly against white-box attacks. The hybrid ‎model proposes a possible approach toward real-time seizure detection in clinics, which ‎besides being more accurate can be adversarailly robust as well. The contributes to the current ‎body of literature on seizure detection a fully integrated approach toward robust behavior in ‎practical medical environments‎.